2015
DOI: 10.1155/2015/161579
|View full text |Cite
|
Sign up to set email alerts
|

T, B, and NKT Cells in Systemic Inflammation in Obstructive Sleep Apnoea

Abstract: Background. Obstructive sleep apnoea syndrome (OSAS) brings risk of serious complications. The study objective was to assess elements of the cellular immune response in the course of OSAS. Methods. Peripheral blood (PB) lymphocytes: T, B, NK, NKT-like, Th, Tc, and HLA DR+ T cells were evaluated by flow cytometry of 48 OSA patients; the concentration of adiponectin, interleukin 1β, and TNFα was measured by ELISA method. The OSA complication score was developed and used for statistical analysis. Results. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
2
22
1
1
Order By: Relevance
“…OSA patients have increased number of CD8+ and decreased number of CD4+ cells, which were related to AHI. [31][32][33] Elevated levels of CD8 + cells were also found in patients with bronchiectasis, which also supported the role of T lymphocyte in the pathogenesis of primary bronchiectasis. 34,35 In our study, the correlation analysis showed that the bronchiectasis score of severity and extent related to the values of CD8 and CD4/CD8.…”
Section: Discussionsupporting
confidence: 52%
“…OSA patients have increased number of CD8+ and decreased number of CD4+ cells, which were related to AHI. [31][32][33] Elevated levels of CD8 + cells were also found in patients with bronchiectasis, which also supported the role of T lymphocyte in the pathogenesis of primary bronchiectasis. 34,35 In our study, the correlation analysis showed that the bronchiectasis score of severity and extent related to the values of CD8 and CD4/CD8.…”
Section: Discussionsupporting
confidence: 52%
“…In 52% of patients, features of metabolic syndrome were recognized. Distribution of patients in each group of OSAS complication score (defined according to [3]) was as follows: score 0 (4), score 1 (14), score 2 (19), score 3 (7), score 4 (4), and score 5 (1). Hypertension was recognized in 72% and COPD in 7% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we confirmed the significance of adiponectin in the inflammatory process in OSAS as well as its complications. Adiponectin concentration to BMI ratio (A/BMI) correlated with the OSA complication score: the lower A/BMI index, the higher the risk of cardiovascular and metabolic complications of OSAS [3]. This study presents an important finding: Fas-positive cells and the concentration of soluble Fas were accompanied by a low value of A/BMI ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations